Self-Diagnosis and Self-Reconfiguration of Piezoelectric Actuator and Sensor Network for Large Structural Health Monitoring - Dong Liang; Liaoni Wu; Zhifeng Fan; Yang Xu (International Journal of Distributed Sensor Networks)
For large structural health monitoring in practical applications, the sensor failure in large sensor network will generate the failure of the damage evaluation or the leaving of unmonitored area in a large structure. Hence, in order to realize a real-time and reliable evaluation for the large structural damage and satisfy the requirement of advanced maintenance of the structure, the paper introduces an efficient piezoelectric sensor failure monitoring approach integrated with self-diagnosis and self-reconfiguration reasoning method. Firstly, the developed method is introduced for large structural health monitoring. Then, the effects of piezoelectric actuator and sensor bonding defects on Lamb wave propagations are investigated in a real-world monitoring experiment for the large aviation aluminum plate. Lastly, the self-diagnosis and self-reconfiguration method of piezoelectric actuator and sensor network for large structural health monitoring based on Lamb wave for the passive and active damage monitoring is verified in the experiment. Based on the results shown in the experiment, a big potential in real-time application demonstrates that the method can accurately and rapidly identify the sensor failure by reasoning and analyzing Lamb wave propagations using proposed methods.